The Effectiveness of CBT on Perceived Social Support, Cultural Competence, and Financial Stress in Depressed Women - Forghani Elahabadi, Fatemeh (Psychology of Woman Journal, 2023)
Objective: This study aimed to evaluate the effectiveness of Cognitive Behavioral Therapy (CBT) in enhancing perceived social support and cultural competence while reducing financial stress among depressed women.Methods and Materials: A randomized controlled trial was conducted with 30 women from Tehran, divided into an intervention group and a control group, with 15 participants in each. The intervention group received eight 90-minute CBT sessions over two months, while the control group received no intervention. Data were collected at baseline, post-intervention, and at a five-month follow-up. Repeated measures ANOVA was performed to analyze differences across time points, followed by Bonferroni post-hoc tests to assess specific changes. SPSS software (version 27) was used for all statistical analyses.Findings: The repeated measures ANOVA revealed significant improvements in the intervention group compared to the control group for all three variables. Perceived social support showed a significant between-group effect, F(1, 28) = 12.34, p = 0.001, with a large effect size (η² = 0.31). Cultural competence also had a significant effect, F(1, 28) = 14.76, p = 0.0008, with an effect size of 0.34. Financial stress was significantly reduced, F(1, 28) = 10.89, p = 0.002, with an effect size of 0.28. Bonferroni post-hoc tests confirmed these results, showing significant improvements in perceived social support (p = 0.002), cultural competence (p = 0.003), and a reduction in financial stress (p = 0.001).Conclusion: Cognitive Behavioral Therapy significantly improves perceived social support and cultural competence while effectively reducing financial stress among depressed women. These findings suggest that CBT is a comprehensive and culturally adaptable intervention for addressing multiple dimensions of psychological and socioeconomic distress, with benefits that may be sustained over time.